PERLINDUNGAN HUKUM TERHADAP PELAKU USAHA DAN PENGGUNA JASA TRANSPORTASI OJEK ONLINE DALAM PERKEMBANGAN DINAMIKA HUKUM DAN MASYARAKAT - Nanin Koeswidi Astuti (Fakultas Hukum Universitas Kristen Indonesia, 2019)
Abstract Online transportation is the development of the world of transportation and communication that is inseparable from the development of increasingly advanced, sophisticated science and technology so that it produces various innovations in creating goods or services products, online transportation is one of the results of technological and communication advancement innovations. The regulation of public transport in Indonesia is regulated in Law No. 22 of 2009 concerning Road Traffic and Transportation (LLAJ), PP No. 74 of 2014 concerning Road Transportation, until now in Indonesia there are no legal regulations specifically regulating online motorcycle taxi transportation, there is a legal vacuum with no online motorcycle taxi arrangements. Until now there has been no law which regulates public transportation of motorcycle taxi online, this causes legal protection for business operators or businessmen providing online motorcycle taxi services and users of online motorcycle taxi services whose legal protection is unclear. Keyword: businessman, online transportation services, online motorcyle.